Design and Development of Interactive Multimedia Based on Didactical Design for Basic Programming Subject: Branching Material - Faradissa Nurul Faidah (Universitas Pendidikan Indonesia, 2021)
Basic Programming is subject that being learn by Engineering Computer’s students. The branching material is proven difficult for students to understand and implement it. Learning obstacle in Basic Programming can occur due to inaccurate teaching materials and learning models used, resulting in students do not understand and interested in learning it deeply. This study aims to determine impact of the use of interactive multimedia based on didactical design to respond the learning obstacle based on student learning outcomes. This research was conducted with Pre-Experimental with One-Group Pretest-Post-test design and multimedia research Lifecycle Method in class XI Software Engineering Vocational High School 2 Cimahi. The results of this study can be concluded: 1) Didactical design that is implemented into interactive multimedia consists of explanations any kind of branching in basic programming and exercises designed to respond to students' learning obstacle on branching material; 2) Based on the gain value obtained after implementing interactive multimedia based on didactical design on branching material of 0.59 is interpreted as